2013
DOI: 10.1371/journal.pone.0055362
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genetic Alterations within the PI3K Pathway Are Responsible for AKT Activation in Patients with Ovarian Carcinoma

Abstract: The phosphatidylinositol 3-kinase (PI3K)/AKT pathway is activated in multiple cancers including ovarian carcinoma (OC). However, the relative contribution of the single components within the PI3K pathway to AKT activation in OC is still unclear. We examined 98 tumor samples from Italian OC patients for alterations in the members of the PI3K pathway. We report that AKT is significantly hyperactive in OC compared to normal tissue (n = 93; p<0.0001) and that AKT activation is preferentially observed in the elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 61 publications
0
24
1
Order By: Relevance
“…This alteration might be a key factor to enhance the effect of PIK3CA amplification in activating AKT/mTOR pathway and driving tumorigenesis. In most OC cases, PIK3CA (also called p110) and PIK3R1 (also called p85α) were overexpressed [12]. However, in the present case, a mutation in the inhibitory iSH2 domain of PIK3R1 was reported in coordination with PIK3CA amplification.…”
Section: Discussioncontrasting
confidence: 48%
“…This alteration might be a key factor to enhance the effect of PIK3CA amplification in activating AKT/mTOR pathway and driving tumorigenesis. In most OC cases, PIK3CA (also called p110) and PIK3R1 (also called p85α) were overexpressed [12]. However, in the present case, a mutation in the inhibitory iSH2 domain of PIK3R1 was reported in coordination with PIK3CA amplification.…”
Section: Discussioncontrasting
confidence: 48%
“…As the FOS transcription factor controls some of the same downstream targets of the PTEN-mTOR pathway (Koul et al 2007;De Marco et al 2013), it is possible that the genetic background of a boxer could make them more sensitive to a mutation in the PTEN-mTOR pathway in relevant cell types compared to the average dog. It has been shown that genetic background predisposes to specific cancers, even specific lymphoma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, overexpression of SGK3 significantly correlates with poor overall survival of HCC patients ( P = 0.028) 20. However, in contrast to these studies demonstrating a role for SGK3 in AKT-independent oncogenic signaling, a recent report failed to demonstrate a role for SGK3 in mediating aberrant PI3-K activity in a panel of ovarian tumor samples exhibiting low AKT activation 89. Specifically, tumors presenting with low phosphorylated AKT but with high PIK3CA , SGK3 activation was detected in only 36% of ovarian tumors, and SGK3 phosphorylation did not correlate with phosphorylated PIK3CA overexpression or AKT activation.…”
Section: Akt-independent Pi3-k Signaling To Cancermentioning
confidence: 97%